The Quest for Authenticity and Self-discovery in Education with Special Attention Paid to Language Education - Rumianowska, Agnieszka (Studia Edukacyjne, 2020)
The purpose of the article is to contribute to the discussion about the relevance of existential issues in contemporary education. The analyses presented in the paper are related to the problems of self-reflection, self-questioning and the process of spiritual and moral development of human beings. Firstly, the author begins by depicting the meaning of human existence in the light of philosophy. What is at issue here is a question of being oneself, recognizing personal truth and finding one’s own voice as opposed to being inauthentic or fleeing from oneself. Special attention is paid to the language as an essential, constitutive element of being. Secondly, the article attempts to consider some educational implications resulting from the deep ontological relationship between human beings and language. Describing them, the author indicates that ignoring vital questions in language education contributes to spiritual vacuity in the lives of young people and reduces educational thinking merely to instrumental, pragmatic problems concerned with qualification and transfer of communicative skills.